Estimation of expected years of life lost for patients with ischemic stroke and intracerebral hemorrhage. Issue 5 (13th June 2019) - Butsing, Nipaporn; Tipayamongkholgul, Mathuros; Ratanakorn, Disya
Abstract : Purpose: The purpose of this paper is to estimate the mean life expectancy (LE) and the expected years of life lost (EYLL) for ischemic stroke and intracerebral hemorrhage. Design/methodology/approach: This retrospective cohort study included 5, 210 patients with a diagnosis of first ischemic stroke or intracerebral hemorrhage between 2005 and 2013 from Ramathibodi Hospital, Bangkok, Thailand. The survival of each case was followed until December 31, 2016. A semiparametric extrapolation method was applied to estimate the lifetime survival function relative to an age and sex-matched reference population. Findings: Of 5, 210 patients, 74.2 percent experienced ischemic stroke. About 54.3 percent were men. Mean age at diagnosis was 64.3 years. The mean LE was 12.5 years for ischemic stroke and 12.0 years for intracerebral hemorrhage. The EYLL among patients with intracerebral hemorrhage was significantly higher than among those with ischemic stroke (10.1 vs 5.7). Women were expected to lose more LE than men for both types of stroke ( p -value<0.05), while younger aged patients were expected to lose more years of life than older ones. Originality/value: This study fulfilled an identified need to estimate LE and EYLL among patients with ischemic stroke and intracerebral hemorrhage.